Totalitarianism and music in the context of the 20th century - Vecumnieks, Andris; Kurpniece, Baiba (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
The article Totalitarianism and Music evaluates the system of totalitarianism and realization of its ideologies in arts. The article does not aspire to provide comprehensive and detailed analysis of totalitarianism, its purpose is to create an informed impetus for further in-depth studies of totalitarianism, the objectives are to (1) comprehend the totalitarian systems and the musical culture politics established in 1930ies by the most notable examples of totalitarianism – USSR and Germany (3rd Reich), (2) to compare these examples, highlighting the main ideological conceptions of the realization of the aforementioned culture politics (socialistic realism, songs of masses, degenerate music, censorship, ceremonial, music outside the law, et al), (3) to observe differences and similarities in the perceptions of the ideological criteria of “correct” art (principle of party and principle of nationalism), (4) to define the place and role of the artist – creative personality – in these systems. The work employs methods based on research of scientific and journalistic sources, audio and video documents that capture processes of the given time period, personal competencies of composer and conductor, as well as other available materials. The conclusion of the article offers a comparison of similarities and differences of music politics in totalitarian systems. Fundamentally, several similar totalitarian ideologies and mechanisms of artistic control exist; differences hide within their realization and concept of priorities, as well as in the general perception and view of culture politics. Music and arts are subject to control exerted by party and ruling elite; the term music outside the law is clearly defined. Musical and ideological upbringing objectives facilitate its purpose for wide social strata (music in factories, for town squares, for working people, etc). The relative competence of the leaders (Y. Stalin and A. Hitler) in music history and musical processes, their general interest in music and arts, as well as desire and pleasure to act as “enlightened rulers” facilitated spreading of specific musical taste and comparatively proficient evaluation of musical tendencies, as well as valid concept definitions. The “ideological” composer of both systems was Beethoven, confirming the universal nature of his music. In the Soviet Union the mass musical education was realized through new music of social realism, reflecting the ideology of the regime. The culture politics of the 3rd Reich prioritized values of classical music. The USSR differentiated music and art according to their ideological characteristics, declaring the aesthetics of social realism and mass songs the cornerstones of its culture ideology. In Germany, however, music and arts were differentiated according to national characteristics (degenerate art). In contrast with the communist ideology of ceremonial and commissioned music, Germany forbids composition of dedications to individuals or to party. The juxtaposition of mass song and academic music, as well as the contrasting attitudes towards innovative elements in art are the most significant differences between both totalitarian culture politic systems.